2019
DOI: 10.2217/hep-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic translocation of nuclear LSD1 ( KDM1A ) in human hepatoma cells is induced by its inhibitors

Abstract: Aim: Histone-modifiable lysine-specific demethylase-1 (LSD1/KDM1A) is an oncoprotein upregulated in cancers, including hepatoma. We previously reported that the hepatoma-preventive geranylgeranoic acid (GGA) inhibits KDM1A at the same IC 50 as that of the clinically used tranylcypromine. Here, we report that these inhibitors induce the cytoplasmic translocation of nuclear KDM1A in a human hepatoma-derived cell line. Methods & results: Immunofl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is a critical factor for mammalian development and many cellular processes (Shi et al, 2004). KDM1A constitutes a potential epigenetic target for drug therapy as suggested by its homology with MAOB in structure (Yabuta & Shidoji, 2019). An increasing number of researches have validated that the high expression levels of KDM1A is related to the poor prognosis of multiple cancers (Huang et al, 2017; Maiques‐Diaz & Somervaille, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is a critical factor for mammalian development and many cellular processes (Shi et al, 2004). KDM1A constitutes a potential epigenetic target for drug therapy as suggested by its homology with MAOB in structure (Yabuta & Shidoji, 2019). An increasing number of researches have validated that the high expression levels of KDM1A is related to the poor prognosis of multiple cancers (Huang et al, 2017; Maiques‐Diaz & Somervaille, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…GGA [XI] and several of its dihydro derivatives inhibited active recombinant human LSD1 ( 100 ). Furthermore, GGA treatment of HuH-7 cells resulted in rapid migration of nuclear-localized LSD1 to the cytoplasm ( 101 ), indicating that GGA [XI] may have epigenetic effects on cells.…”
Section: Other Biological Functions Of Ggamentioning
confidence: 99%
“…LSD1 is mainly localized in the nucleus, while pharmacological intervention could cause a translocation of LSD1 from the nucleus to the cytoplasm ( Yabuta and Shidoji, 2019 ). In tau pathology, Christopher et al (2017) found LSD1 is localized to tau aggregates and sequestered in the cytoplasm, and proposed that the reduction of LSD1 in nucleus impairs the survival of hippocampal and cortical.…”
Section: Lysine-specific Demethylase 1 and Tau Proteinmentioning
confidence: 99%